Health professionals' perspectives on clinical challenges in managing hypertensive disorders of pregnancy and recommendations for improving care: A multi-center qualitative study - Kwame Adu-Bonsaffoh; Kwame Adu-Bonsaffoh; Kwame Adu-Bonsaffoh; Evelyn Tamma; Adanna Uloaku Nwameme; Joyce L. Browne (Frontiers in Global Women's Health, 2022)
BackgroundHypertensive disorders of pregnancy (HDP) are a leading cause of maternal mortality and morbidity globally despite the intensive international effort to improving maternal care. Substandard clinical care has emerged as a major contributing factor to the high maternal deaths associated with maternal hypertension globally and the impact is severer in low- and middle-income countries (LMICs). Context specific challenges impact negatively on the quality of maternity care and health providers play a crucial role in achieving positive pregnancy experiences for women. This study explored the perspectives of health professionals on the clinical challenges associated with the management of HDP in Ghana and recommendations for improving care.MethodsA multi-center qualitative study using in-depth interviews (IDIs) was conducted in five major hospitals in the Greater Accra Region of Ghana between June 2018 and March 2019. Health professionals (midwives/nurses and medical doctors) who have worked at the study sites for at least three months were included. Data were analysed based on thematic content using Nvivo software.ResultsWe included 62 health professionals comprising 40 midwives/nurses (64.5%) with a median age of 32.5 years (range 26 to 59) and 22 medical doctors (34.5%) with a median age of 34 years (range 25 to 55). Health providers highlighted major challenges associated with clinical management of hypertension in pregnancy: (1) patient-related factors (inadequate understanding and misconceptions about hypertension in pregnancy, women's non-compliance with clinical advice, financial constraints); (2) health system-related challenges (frequent unavailability of logistics, medications and laboratory support, delays in provision of care and limitations in the health insurance coverage); (3) health provider associated factors (inadequate number of health professionals and poor attitudes). Context-specific recommendations suggested for improving the quality of care in managing maternal hypertension include restructuring of the health system to reduce delays in providing care, improving financial coverage of medical insurance, encouraging social/family support, enhancing education on HDP and strengthening the health workers’ numbers and working conditions.ConclusionMajor challenges in the clinical management of HDP relate to the health system, health professionals and pregnant women themselves. Context-specific interventions are required to improve the quality of care for hypertensive mothers including regular health education, re-structuring of the health systems, refresher courses for health providers, improvement in health insurance coverage and government subsidy for hypertensive women.